Calculating transcription factor binding maps for chromatin - Teif, Vladimir; Rippe, Karsten (Briefings in bioinformatics, 2012)
Abstract. Current high-throughput experiments already generate enough data for retrieving the DNA sequence-dependent binding affinities of transcription factor